Microsoft OneNote 2013 plain & simple - Weverka, Peter (Microsoft Press, 2013)
Follow the book's easy steps and screenshots and clear, concise language to learn the simplest ways to organize information and manage your work and personal lives. You'll learn to: take notes, organize, and share them; bookmark and tag notes for easier searching; add pictures, drawings, and spreadsheets; handwrite notes and convert them to text; record audio and video notes; access notes from the web or mobile device. --
Print version record
Keywords: Microsoft OneNote; Note-taking -- Computer programs; Business -- Computer programs; Prise de notes; Logiciels; Business; Computer programs